(untitled) (Proceedings of International Conference on Special Education, 2025)
The Alternative Learning System (ALS) enables flexible and non-formal basic education for out- of-school children, youth and adult individual with diverse learning needs, abilities and capabilities. It provides vital educational opportunities to those who have not had access to or have dropped out in formal education. Nonetheless, those with disabilities in ALS encounter additional barriers to acquiring literacy skills, which makes it impossible for them to qualify for the A&E assessment on Elementary and Junior High School level. This stagnates their academic and certification advancement opportunities. To address these challenges, this action research used descriptive-quantitative analysis to gather insights from 30 ALS teachers on innovative strategies to support learners with disabilities. These strategies include the integration of Artificial Intelligence (AI) through assistive technologies, adaptive learning platforms, and differentiated instruction. Findings revealed that assistive technologies received the highest mean rating of 3.95, with teachers strongly agreeing on their value. Adaptive learning platforms and differentiated instruction also received high ratings, with mean rating of 3.89 and 3.87 respectively. Overall, ALS teachers strongly agree and support the use of AI- driven strategies to enhance learning for learners with disabilities. The results highlight the importance of investing in technology-based solutions and teacher training to effectively implement these approaches. This study offers practical recommendations for educators, policymakers, and curriculum developers, emphasizing the transformative role of AI in Alternative Learning System education.